Clinical and demographic characteristics of influenza B outbreak in Erzincan province of Turkey - Ünver, Edhem; Çıkman, Aytekin; Karakeçili, Faruk (Journal of Surgery and Medicine, 2019)
Aim: Seasonal epidemics of influenza are responsible for significant morbidity and mortality worldwide. We aimed to investigate distribution of seasonal influenza viruses, and clinical and demographic characteristics of influenza B epidemics in Erzincan province of Turkey. Methods: A total of 103 patients who presented to our hospital in spring the season in accordance with influenza case management schema in line with the recommendations by the World Health Organization and Ministry of Health were included in this study. Cepheid SmartCycler system, which is an integrated RNA replication and detection device based on microprocessor controlled I-CORE® (Intelligent Cooling / Heating Optical Reaction) module was used in order to detect Influenza A / Influenza B viruses. Results: Influenza was positive in 28 (27.1%) of all patients who presented with suspected Influenza, with 23 (22.3%) being Influenza B and 5 (4.9%) Influenza A. Of patients with positive Influenza B, 18 (78%) had one or more chronic diseases. Of the patients, 15 (65%) were diagnosed with one of the chronic pulmonary disease, 8 (35%) one of the chronic cardiac diseases, and 3 (13%) diabetes mellitus. Leukopenia and thrombocytopenia were more common than leucocytosis. Seven patients were followed-up as inpatients. At the follow-up period, three of the patients were taken to the intensive care unit and 2 of them died. Whereas the remaining patients were discharged with recovery. Conclusion: We observed that, Influenza B progressed more seriously than we expected. For this reason, we think that immunity level of the community against Influenza B should be raised with vaccination campaigns involving different subtypes of Influenza B.